Perancangan Arsitektur Enterprise TOGAF Pada Menu Pengajuan Semester Pendek Web Student Amikom - Fadilah Musafiroh; El Syafangatun Aulia Difa; Iis Sahita; Farah Setyaningsih; Tarwoto (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The design of the short semester application menu on Universitas Amikom Purwokerto's student web platform using the TOGAF ADM framework aims to create an efficient, structured, and user-friendly information system. The design process begins with the Preliminary Phase to define the scope and continues to the Technology Architecture, ensuring the use of modern, scalable, and secure technology. Business processes are modeled using BPMN to enhance workflow transparency and efficiency, while data and application architecture ensure accurate information management and optimal system integration. This system allows students to apply for short semesters online, process payments, and receive real-time verification. The implementation supports the university's strategic vision of delivering modern, efficient, and technology-driven academic services while improving user experience and operational efficiency in academic administration.